1993
DOI: 10.1111/j.1476-5381.1993.tb12874.x
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin receptors of the NK2 type involved in the acetylcholine release by nicotine in guinea‐pig bladder

Abstract: 1 The effects of guanethidine and tachykinins on nicotine-and electrical stimulation-induced cholinoceptor responses were studied in isolated urinary bladder from the guinea-pig. 2 Acetylcholine release and the contractile response stimulated by nicotine were partially reduced by a sympathetic nerve blocker, guanethidine. Neurokinin A (but not substance P methyl ester or senktide) enhanced both acetylcholine release and contraction by nicotine in the presence of guanethidine. 3 Frequency-contraction curves (1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…The activity of TTX-sensitive and atropine-resistant contractile components was nearly abolished by α,β-mATP targeting purine P2X receptors; this phenomenon is likely attributable to neurogenic ATP ( fig. 1 ) ings that both neurogenic ACh and ATP contribute to EFS-induced UBSM contractions are similar to those of previous reports describing the characteristics of EFSevoked contractions in mice, guinea pig, and human UB tissues [26,27,[29][30][31] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The activity of TTX-sensitive and atropine-resistant contractile components was nearly abolished by α,β-mATP targeting purine P2X receptors; this phenomenon is likely attributable to neurogenic ATP ( fig. 1 ) ings that both neurogenic ACh and ATP contribute to EFS-induced UBSM contractions are similar to those of previous reports describing the characteristics of EFSevoked contractions in mice, guinea pig, and human UB tissues [26,27,[29][30][31] .…”
Section: Discussionsupporting
confidence: 89%
“…Although ACh is a primary mediator to trigger UB contraction during a micturition reflex, pharmacological studies have shown that adenosine triphosphate (ATP) plays a small but substantial role in electrical field stimulation (EFS)-induced UB contractions [23][24][25][26][27][28][29] . Given the pharmacological characteristics of distigmine, its restorative effects on impaired UB contractile functions are likely produced through the exclusive potentiation of ACh-induced contractile responses of UBSM; however, this has not been shown with functional studies in EFS-evoked UBSM contractions.…”
mentioning
confidence: 99%
“…Sustained release of neurotransmitter-like substances occurs in the bladder, analogous to the experimental incubation of the agonists in this study. Acetylcholine and ATP can be released due to nervous activity, and, more notably, non-neuronal activities, such as stretches during normal bladder filling and distension ( 37 , 40 , 41 ), bladder contractions ( 28 , 42 ), spontaneous release ( 28 , 42 44 ), and stimulation by inflammatory mediators ( 45 50 ) accumulated in the tissue under pathological conditions and during aging. The tonic release of neurotransmitters due to parasympathetic activity during bladder storage may also occur ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore disruption of the preprotachychynin gene which encodes for substance P, leads to an impaired response to chemical irritation of the urinary tract in mice (Kiss et al, 2001). Neurokinin A and substance P also have an excitatory effect on autonomic ganglia in the bladder (Kawatani et al, 1989;Shinkai et al, 1993) and on bladder smooth muscle (Maggi, 1997b). Thus Substance P or a related neurokinin may be an excitatory transmitter in bladder afferent pathways in the peripheral and central nervous system.…”
Section: Introductionmentioning
confidence: 99%